2020
DOI: 10.3892/etm.2020.9215
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of TNF‑α and IL‑10 gene polymorphisms with primary nephrotic syndrome

Abstract: The study explored the correlations of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) gene polymorphisms with susceptibility and the condition of primary nephrotic syndrome. A total of 200 patients with primary nephrotic syndrome in Qilu hospital were collected as disease group, and 200 healthy people were selected as control group. Genomic deoxyribonucleic acids (DNAs) of nucleated cells in the peripheral blood were extracted to detect the gene polymorphisms of TNF-α (rs1799724 and rs1800629) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Six literatures from five countries were enrolled including China, Egypt, Iran, Romania, and India. 18 , 25 , 26 , 27 , 28 , 29 Table 3 describes the whole data and information. Table 4 describes the whole NOS results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six literatures from five countries were enrolled including China, Egypt, Iran, Romania, and India. 18 , 25 , 26 , 27 , 28 , 29 Table 3 describes the whole data and information. Table 4 describes the whole NOS results.…”
Section: Resultsmentioning
confidence: 99%
“…Informed consent was obtained from all participants. Detailed demographic characteristics such as age, sex, body mass index (BMI), smoking status, and alcohol Xiao et al 25…”
Section: Participates Characteristicsmentioning
confidence: 99%
“…In a small pediatric study, TNF was shown to be higher during times of relapse (mean 4.11 pg/ml) and lower during remission (2.14 pg/ml) for steroid sensitive nephrotic syndrome, while there was no significant difference in TNF for SRNS children who remained protienuric after treatment (6.13 vs. 5.67 ng/ml) (Weisbach and GBea 2017 ). Further, genomic studies have found polymorphisms in TNF associated with the susceptibility for nephrotic syndrome and transcriptomic studies have shown activation of TNF in children and adults with nephrotic syndrome (Mariani LESea n.d); (Xiao 2020 ). In an animal model, rats infused with TNF developed proteinuria; however, the exact mechanism by which cytokines result in proteinuria is unclear (Lai et al 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…TNF is primarily produced by mononuclear macrophages and can prevent the body from the infringement by killing tumor cells. It is also proved to be an important cytokine with a wide range of biological effects, which is connected with the susceptibility and development of immune diseases, including NS [ 49 ].…”
Section: Discussionmentioning
confidence: 99%